Unveiling the Landscape of PD-L1 Expression and Tumor-Infiltrating Lymphocyte Subtypes in Advanced Triple-Negative Breast Cancer in Brazil - Dos Santos ALS; Da Silva JL; De Albuquerque LZ; Neto ALA; Da Silva CF; Cerva LAM; Small IA; Rodrigues FR; De Macedo FC; Marcelino CP; Batista PDM; Rego MADC; et al. (Breast Cancer: Targets and Therapy)
Alexssandra Lima Siqueira Dos Santos,1 Jesse Lopes Da Silva,1 Lucas Zanetti De Albuquerque,1 Antônio Lucas Araújo Neto,1 Cecília Ferreira Da Silva,1 Luana Aguiar Mesquita Cerva,1 Isabele Avila Small,1 Fabiana Resende Rodrigues,2 Fabiane Carvalho De Macedo,2 Cicera Pimenta Marcelino,3 Paula de Mendonça Batista,3 Maria Aparecida do Carmo Rego,3 Maria Amélia Carlos Souto Maior Borba,3 Andreia Cristina De Melo1 1Division of Clinical Research and Technological Development, Brazilian National Cancer Institute, Rio de Janeiro, Brazil; 2Division of Pathology, Brazilian National Cancer Institute, Rio de Janeiro, Brazil; 3MSD Brazil, São Paulo, BrazilCorrespondence: Maria Amélia Carlos Souto Maior Borba, MSD Brazil, Avenida Chucri Zaidan, 296 - 11° andar, Edif. Torre Z Vila Cordeiro, São Paulo/SP, Brazil, 04583-110, Tel +55 11 98293-9203, Email amelia.borba@merck.comPurpose: This study aimed to assess the frequency and prognostic significance of programmed cell death ligand 1 (PD-L1) expression and tumor-infiltrating lymphocyte (TIL) subtypes in advanced triple-negative breast cancer (TNBC).Patients and Methods: A database search was conducted to identify women with previously untreated locally recurrent inoperable or metastatic TNBC treated between January 2018 and December 2022. The inclusion criteria required formalin-fixed paraffin-embedded samples aged less than four years. PD-L1 expression was evaluated using the PD-L1 IHC 22C3 pharmDx assay, and the combined positive score (CPS) was calculated. TIL subtypes were assessed using immunohistochemical staining.Results: The study included 150 patients, with a median age of 51.5 years. The majority of patients were younger than 65 years, postmenopausal, non-white, and had metastatic TNBC. CPS≥ 10 was observed in 20.9% of cases, mainly in postmenopausal women. No significant differences were found in demographic characteristics and clinicopathological variables across PD-L1 subgroups. Tumors with PD-L1 CPS≥ 10 had higher expression of CD3+, CD4+, and CD8+ TIL subtypes. Most patients received first-line chemotherapy, with smaller proportions undergoing second, third, and fourth-line treatments. No statistically significant differences were observed in median progression-free survival (PFS) or overall survival (OS) across PD-L1 subgroups in this cohort of chemotherapy-treated patients.Conclusion: This study provides insights into the expression profiles of PD-L1 and TIL subtypes in advanced TNBC. The PD-L1 CPS status did not significantly affect survival outcomes, but variations in TIL subtype composition were observed based on PD-L1 CPS status.Keywords: triple-negative breast cancer, PD-L1 expression, tumor-infiltrating lymphocytes, immunohistochemistry, molecular epidemiology, progression-free survival